PROJECT BASED PANCASILA ECONOMIC LEARNING FOR STUDENTS OF ELEMENTARY SCHOOL - Silky Roudhotus Sa'adah; M.Thoha Ainun Najib; Efa Wahyu Prastyaningtyas (Universitas Pendidikan Indonesia, 2023)
Pancasila economy is an economic system imposing a joint venture based on kinship and cooperation to symbolize Indonesian identity which is not possessed by another country. Besides, the Pancasila economy is the philosophical foundation and the 1945 constitution (UUD 45) is the constitutional foundation of Indonesia. This research aimed to describe how the implementation of Project-Based Pancasila Economic Learning through the Experiential Learning method. Project-based done, of course, adjusts to students who are still elementary school age. This research used an action research approach in Public Elementary School Blitar, Indonesia, the research subject was 70 elementary students. Data collection was conducted by interview, questionnaire, and Forum Grup Discussion (FGD). The research finding showed that the students were able to interpret that economic learning could be conducted outside the class. By experiential learning method, the students were expected to be more understand the purpose of Pancasila Economic learning. In addition, based on the learning mentioned, the students could understand and implement the form of Pancasila Economic, especially practicing the precepts in everyday life.